2015
DOI: 10.1097/md.0000000000002098
|View full text |Cite
|
Sign up to set email alerts
|

Obese Patients With a Binge Eating Disorder Have an Unfavorable Metabolic and Inflammatory Profile

Abstract: To evaluate whether obese patients with a binge eating disorder (BED) have an altered metabolic and inflammatory profile related to their eating behaviors compared with non-BED obese.A total of 115 White obese patients consecutively recruited underwent biochemical, anthropometrical evaluation, and a 75-g oral glucose tolerance test. Patients answered the Binge Eating Scale and were interviewed by a psychiatrist. The patients were subsequently divided into 2 groups according to diagnosis: non-BED obese (n = 85)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
3
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 46 publications
11
64
3
2
Order By: Relevance
“…Consistent with previous findings in adults with binge eating disorder, 19 we found that youth with LOC eating had significantly higher inflammation, as measured by hsCRP, than those without LOC, even after adjusting for differences in fat mass. Notably, these findings were independent of other factors that might contribute to elevated hsCRP.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with previous findings in adults with binge eating disorder, 19 we found that youth with LOC eating had significantly higher inflammation, as measured by hsCRP, than those without LOC, even after adjusting for differences in fat mass. Notably, these findings were independent of other factors that might contribute to elevated hsCRP.…”
Section: Discussionsupporting
confidence: 81%
“…Based on findings that adults with obesity and binge eating disorder have worse metabolic and inflammatory profiles compared to their counterparts with obesity, but without the disorder, 19 and that youth with reported LOC eating have worse metabolic characteristics than those without LOC eating, 26 we hypothesized that children and adolescents who reported LOC eating would have higher serum concentrations of hsCRP than youth without LOC, after adjusting for adiposity. In addition, given that past research has shown a bidirectional link between psychopathology and inflammation, [28][29][30] and that youth with LOC eating report more psychopathology than youth without LOC eating, 23,31,32 we examined whether depressive symptoms or eating-related psychopathology mediated the relationship between LOC eating and hsCRP concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently from our study, Succurro et al [25] demonstrated an unfavorable metabolic and inflammatory profile only in obese women with BED. They studied 115 obese individuals of both genders and divided them into 2 groups per the presence or absence of binge eating.…”
Section: Resultscontrasting
confidence: 50%
“…In another study of patients with known neurodegenerative diseases, those with co-morbid binge eating disorder had greater atrophy in right-sided orbitofrontal-insular-striatal circuit and were more likely to be diagnosed with frontotemporal dementia [24]. While BED commonly occurs in normal-weight individuals, obese individuals with BED have significantly higher rates of dietary disinhibition, psychiatric comorbidities, and cognitive dysfunction [2527] as well as higher rates of metabolic disorder and increased inflammatory markers [28]. In one study involving body weight matched overweight women, those with BED had greater risk taking behavior, reduced utilization of feedback processing, impaired decision-making and cognitive flexibility [29].…”
Section: Introductionmentioning
confidence: 99%